The importance of epistemological reflection in design: Approach to the epistemological configurations of design. From logical positivism to complex systems - Zambrano, Marcelo (UNIVERSIDAD DE SONORA, 2022)
The practice of design is defined by processes of research and delimitation of problems generally related to social environments. Therefore, the elements that make up the research processes: epistemology, theoretical perspectives, methodology, and methods, should be presented clearly and concisely, however, epistemological positions have not been taken into account in design projects. This article proposes to point out these underlying positions in some methodological design proposals through a review of the approaches of Bruce Archer and Christopher Alexander, who approach and configure their epistemological positions from logical positivism. Based on these points, it is proposed to review the possibilities of abductive reasoning in the face of inductive and deductive inferences closer to paradigms of empirical sciences. This text proposes a clearer approach and exposition of the epistemological reflections in the design processes, which would allow deepening in the investigation and more complex approaches in theoretical and methodological terms in the projects approached by designers and designers.